2013
DOI: 10.1021/jm4002346
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyldihydroquinazolinone Derivatives of Retro-2 with Enhanced Efficacy against Shiga Toxin

Abstract: The Retro-2 molecule protects cells against Shiga toxins by specifically blocking retrograde transport from early endosomes to the trans-Golgi network. A SAR study has been carried out to identify more potent compounds. Cyclization and modifications of Retro-2 led to a compound with roughly 100-fold improvement of the EC50 against Shiga toxin cytotoxicity measured in a cell protein synthesis assay. We also demonstrated that only one enantiomer of the dihydroquinazolinone reported herein is bioactive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 26 publications
3
73
0
Order By: Relevance
“…The following inhibitors were used in this study: brefeldin A (BFA), golgicide A, and bafilomycin A1 (all from Sigma-Aldrich) and Retro-2 (EMD Millipore). Retro-2c and Retro-2.1 were synthesized inhouse (41,42). The effect of various drugs on cell viability was measured using the CellTiter-Glo assay (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The following inhibitors were used in this study: brefeldin A (BFA), golgicide A, and bafilomycin A1 (all from Sigma-Aldrich) and Retro-2 (EMD Millipore). Retro-2c and Retro-2.1 were synthesized inhouse (41,42). The effect of various drugs on cell viability was measured using the CellTiter-Glo assay (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…High-throughput screens for small-molecule inhibitors of ricin toxicity have recently identified Retro-2 to be a specific blocker of retrograde transport acting at the endosome-TGN interface (59), and it has been shown that Retro-2 and more potent derivatives (41,42) block retrograde transport of ricin and Shiga toxin by displacing STX5 from the TGN toward small peripheral vesicles (42,59). In agreement with our STX5 siRNA data, treatment of HeLa cells with the cyclized analog Retro-2 cycl significantly decreased AAV2-Luc transduction in a dose-dependent manner, showing a reduction of approximately 80% at the highest soluble concentration of 100 M (Fig.…”
Section: Inhibition Of Aav Transport By Compounds Affecting Stx5mentioning
confidence: 99%
See 1 more Smart Citation
“…3E). During the course of our study, structure-activity relationship (SAR) studies focusing on Retro-2 optimization lead to cyclic analogues with an ∼100-fold improvement in the EC 50 against Shiga toxin (Noel et al, 2013). We therefore also investigated whether inhibition of retrograde transport through an improved (i.e.…”
Section: Stxb-ss-saporin Translocates From An Endosomal Compartment Tmentioning
confidence: 99%
“…In addition, since only one enantiomer was active on previous dihydroquinazolinones synthesized as racemates, 13 a chiral phase HPLC separation of Retro-2.1 was performed on a ChiralPak IB column (see Experimental Section and Figure 1). No contamination of Retro-2.1a by Retro-2.1b or vice versa could be identified on the chromatograms (Figure 1).…”
mentioning
confidence: 99%